Antimicrobial Efficacy of a New Chlorhexidine-based Device Against Staphylococcus aureus Colonization of Venous Catheters - Kowalewska, Paulina M. (J Infus Nurs, 2018)
Vascular catheters are a major cause of nosocomial bloodstream infections. ChloraLock (ATTWILL Medical Solutions, Inc, West Jordan, UT, and ICU Medical, Inc, San Clemente, CA) is a novel antimicrobial device containing chlorhexidine digluconate (CHG) that is fitted onto a syringe and infuses CHG into the catheter lumen during locking. The objective of this study was to evaluate the antimicrobial efficacy of ChloraLock with in vitro tests and its ability to reduce Staphylococcus aureus contamination of catheters in the external jugular veins of Yorkshire swine. ChloraLock significantly reduced the bacterial load in the in vitro tests by up to 6 log(10) colony-forming units (CFU) and by 3 to 4 log(10) CFU/lumen in vivo in a swine model with 0.9% NaCl catheter locks.